Correlation of laboratory and real marine corrosion for the investigation of corrosion fatigue behaviour of steel components. (September 2019) - Gkatzogiannis, Stefanos; Weinert, Joscha; Engelhardt, Imke; Knoedel, Peter; Ummenhofer, Thomas
Highlights: No previous correlation of real and laboratory corrosion. Three different laboratory corrosion methods were evaluated. Results compared with similar specimens under real marine corrosion. Countable results for the correlation of real and laboratory corrosion. Each laboratory method suits different aspects of real corrosion. Abstract: A correlation of laboratory corrosion methods with real marine conditions is conducted in the present study. Goal was the definition of an appropriate time scale for each investigated laboratory method for the simulation of marine corrosion. The standardized corrosion in a salt spray chamber and in artificial seawater as well as the empirical method of corroding in an electrolytic setup are investigated. The influence of each corrosion method on physical quantities, which affect the fatigue behaviour and are applied in structural engineering, is taken into consideration. Periodical optical inspection of the surface as well as measurements of thickness loss and surface roughness are carried out for long intervals of deposition. The results of these measurements are statistically processed, in order to validate initial assumptions regarding the evolution of the corrosion influence and enable probabilistic prediction of the specific influence of each corrosion method. Additionally fatigue tests are carried out on butt welds, which were pre-corroded in a salt spray chamber and in artificial seawater. These tests are performed sequentially dry and simultaneously, inside artificial seawater, respectively, in order to evaluate the direct influence of these methods on fatigue life. Similar measurements and results from fatigue testing on specimens of parent material, which were corroded for 2 years in real marine environment in the framework of a previous project are used as reference. All investigated and reference specimens were made of structural steel S355. Conclusions regarding the effectiveness of each investigated method and the influence of corrosion on fatigue are drawn and a first-step time correlation of laboratory and real conditions is made.